A systematic review of the content and delivery of clinical knowledge in orthodontic postgraduate programs - Martin Baxmann; Krisztina Kárpáti; Zoltán Baráth (BMC Medical Education)
Abstract Orthodontic postgraduate education plays a critical role in developing clinical competence, yet substantial variability exists in how programs structure, deliver, and assess clinical knowledge. This systematic review aimed to evaluate the content and delivery of clinical knowledge in orthodontic postgraduate programs and their reported impact on trainee competence. The review followed PRISMA 2020 guidelines and a pre-specified protocol. A comprehensive search was conducted across PubMed, Cochrane Library, ERIC, and CINAHL for studies published between January 2000 and December 2024. Gray literature and reference lists were also screened. Eligible studies included randomized controlled trials, cohort studies, and cross-sectional studies involving postgraduate orthodontic students or educators, with interventions related to instructional strategies or clinical knowledge delivery. Qualitative studies and those focused solely on undergraduate or continuing education were excluded. Following duplicate removal, 104 records were screened, and 30 studies met the inclusion criteria after full-text assessment. Study selection and data extraction were performed independently by two reviewers, with discrepancies resolved by a third. Risk of bias was assessed using the Newcastle–Ottawa Scale, and quality of evidence was evaluated using the GRADE framework. Due to heterogeneity in study design and outcome measures, a narrative synthesis was conducted. Instructional strategies included didactic lectures, problem-based learning, scenario-based simulations, digital learning platforms, and structured assessments such as Mini-CEX and OSCE. Feedback-oriented and interactive methods were consistently associated with improvements in clinical reasoning, procedural skills, and learner confidence. However, substantial variability existed in assessment formats and feedback implementation across institutions. Newcastle–Ottawa scores indicated generally strong selection and outcome measurement, though comparability was often limited. GRADE assessments showed most studies were of moderate quality due to inconsistency or imprecision. These findings highlight the need for harmonized, evidence-based frameworks to guide the delivery and assessment of clinical knowledge in orthodontic postgraduate education, while allowing for flexibility based on institutional context. Efforts to standardize assessment strategies and integrate technology-enhanced learning may support improved competence development across diverse programs.